Risk of fragility fracture is aggravated during bone regeneration processes in osteoporotic sheep - Juan J. Toscano-Angulo; Juan Mora-Macías; Pablo Blázquez-Carmona; Juan Morgaz; Rocío Navarrete-Calvo; Jaime Domínguez; Esther Reina-Romo (PLoS ONE, 2025)
Introduction Bone regeneration processes are associated with a systemic skeletal change in bone quality, increasing the risk of fragility fractures. This condition may be aggravated in osteoporotic patients due to their limited osteogenic capacity. This work evaluates the impairment of the bone quality in osteoporotic sheep during a bone regeneration process. It provides a deeper understanding about the complex multiscale dynamics of bone mineral density, microstructure and chemical composition across different bone tissues, locations and time points. Materials and Methods Osteoporosis was induced in fifteen Merino sheep. A critical-size defect was then created in the sheep’s right hind metatarsus and subsequently regenerated using distraction osteogenesis. The animals were randomly sacrificed during bone regeneration, either on days 40 or 100 after surgery. Computed tomography, micro-computed tomography and chemical composition analyses were conducted on different bone tissues (cortical, trabecular and woven) at several skeletal locations (the operated metatarsus, the contralateral one and the iliac crest) to assess the individual bone quality changes relative to the non-osteoporotic time point. Results After osteoporosis induction, the trabecular tissue experienced a 6.4% reduction in the bone mineral density, while no significant changes were reported in cortical tissue quality. During bone regeneration, the operated bone increased significantly the woven ossification whilst the cortical mineral density decreased by 18.7%. Simultaneously, an early deterioration in the microstructure and chemical composition of the trabecular bone was observed in the iliac crest, persisting over time in non-operated trabecular regions. Conclusions Osteoporosis causes uneven degradation to trabecular tissue quality across different bone locations. Furthermore, the bone regeneration process via bone transport in osteoporotic subjects leads to a systemic skeletal disorder that further impairs the bone quality, surpassing the damage caused by osteoporosis alone. This impairment appears to be intensified by the pre-existing osteoporotic condition.